2022
DOI: 10.21873/cgp.20324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GSK-J4 on JMJD3 Histone Demethylase in Mouse Prostate Cancer Xenografts

Abstract: Background/Aim: Histone methylation status is required to control gene expression. H3K27me3 is an epigenetic tri-methylation modification to histone H3 controlled by the demethylase JMJD3. JMJD3 is dysregulated in a wide range of cancers and has been shown to control the expression of a specific growth-modulatory gene signature, making it an interesting candidate to better understand prostate tumor progression in vivo. This study aimed to identify the impact of JMJD3 inhibition by its inhibitor, GSK4, on prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…GSK-J4, a selective inhibitor of KDM6A/B, which are usually aberrantly expressed in cancers, has been found to have significant antitumor efficacy in several cancers. 26 , 30 , 42 , 43 However, the roles of GSK-J4 in retinoblastoma remain unclear. In the present study, we performed CCK-8, EdU incorporation and colony formation assays and found that GSK-J4 obviously inhibited the proliferation of retinoblastoma cells in a concentration- and time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GSK-J4, a selective inhibitor of KDM6A/B, which are usually aberrantly expressed in cancers, has been found to have significant antitumor efficacy in several cancers. 26 , 30 , 42 , 43 However, the roles of GSK-J4 in retinoblastoma remain unclear. In the present study, we performed CCK-8, EdU incorporation and colony formation assays and found that GSK-J4 obviously inhibited the proliferation of retinoblastoma cells in a concentration- and time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“… 46 In addition, in vivo studies also showed the suitable tolerance of GSK-J4 in mice. 26 , 29 , 30 Moreover, some studies have indicated that GSK-J4 could enhance the effectiveness of known anticancer drugs when used in combination. 33 , 43 , 58 Although promising, these results are still preliminary, and further investigations involving more extensive research and clinical trials will be considered soon, similar to other strategies targeting the regulation of H3K27me3, such as PRC2 inhibitors, which have been well studied and entered multiple clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GSK‐J4 also increased the sensitivity of chemoresistant CRC cells to oxaliplatin by reducing the tumor growth rate 50 . A study involving androgen‐positive (AR+) prostate xenografts in mice showed that GSK‐J4 reduced tumor growth in AR+ xenografts, whereas there was no significant effect on AR‐ xenografts 51 …”
Section: Gsk‐j4 As An Anti‐cancer Drugmentioning
confidence: 99%
“…50 A study involving androgenpositive (AR+) prostate xenografts in mice showed that GSK-J4 reduced tumor growth in AR+ xenografts, whereas there was no significant effect on AR-xenografts. 51…”
Section: In-vivo Studiesmentioning
confidence: 99%